PEMBUATAN NATA DE COCO DENGAN PENAMBAHAN UREA, TANPA UREA DAN EKSTRAK TOGE - Imelda Bahar (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Nata de coco is a type of beverage component that is a cellulose compound (dietary fiber) produced from coconut water through a fermentation with the bacterium Acetobacter xylinum process. The process is aerobic fermentation. To use of urea for component of N are limited and there is an opinion about that are dangerous for processed food products, so the nata is made with urea, without urea and by using bean sprout extract. Bean sprouts or plant sprouts are newly grown small come from seed beans that are sown or through germination. After measuring the thickness of the nata starter, it was nata using the bean sprout extract had an average thickness of 1.7 cm, using 1.35 cm urea and without urea the thickness was 0.45 cm in white and the texture was thick.